The "3 Es" of trauma‐informed care in a federally qualified health center: Traumatic Event‐ and Experience‐related predictors of physical and mental health Effects among female patients. Issue 2 (10th December 2020) - Lathan, Emma C.; Selwyn, Candice N.; Langhinrichsen‐Rohling, Jennifer
Abstract: Federally Qualified Health Centers (FQHCs) are a fast‐growing source of healthcare for women with intersectional identities, or those most frequently exposed to and negatively impacted by interpersonal trauma. According to the "3 E" conceptualization of trauma, certain Event ‐ and Experience ‐related characteristics of a trauma predict victims' physical and mental health Effects . The "3 Es" have yet to be studied in female FQHC patients. The current study examined the prevalence of interpersonal trauma and interrelationships among traumatic Event ‐related factors (e.g., cumulative trauma by victim‐perpetrator relationship), Experience ‐related factors (e.g., betrayal, resilience), and Effects (e.g., somatic symptoms, posttraumatic stress (PTS), anxiety/depression, mistrust, reduced sense of safety) among 138 predominantly Black (89.1%) women receiving care at an FQHC in the southeastern U.S. Roughly 65% of participants ( n = 86) endorsed exposure to at least one type of interpersonal trauma. More cumulative trauma was significantly correlated with more somatic, PTS, and anxious/depressive symptoms, and a reduced sense of safety. Experiences of betrayal and/or resilience were better predictors of PTS and anxious/depressive symptoms and lack of safety than Event ‐related factors. Findings support the need for the implementation of trauma‐informed care within community‐based health centers. Healthcare providers should consider women's subjective experience of trauma when screening for exposure and providing trauma‐sensitive care.